THE EFFICACY AND SAFETY OF LONG-TERM SYSTEMIC ACYCLOVIR THERAPY OF NEONATAL HERPES IN IMMUNOCOMPETENT CHILDREN - Mavrutenkov, V.V.; Bolbot, Y.K.; Shvaratska, O.V.; Kazatska, O.V. (World of Medicine and Biology, 2019)
Medical case histories of two male infants born naturally, in term, who developed neonatal Herpes simplex virus type 2 (HSV-2) infections are discussed. Mothers of both infants presented with signs of vesicular rash in the anogenital area at the time of parturitions. In both cases the presented HSV-2 infection had intranatal transmission route. Clinical course of infection was notable for recurrent vesicular rash with no signs of fever or systemic disorders. Both infants were prescribed continuous systemic acyclovir therapy from the early age for over a year. In both cases long-term course of acyclovir was well tolerated and led to long-lasting control of the infection. Therefore such therapeutic regimen might be preferable to the intermittent short-term courses for exacerbations of HSV-1 and HSV-2 infections in infants. Assessment of efficacy and optimal duration of the treatment should be mainly determined by clinical indications.